STUDI NUMERIK KINERJA HEAT SINK BERBASIS ALIRAN DUA FASE DENGAN ETIL ASETAT SEBAGAI ALTERNATIF PENDINGIN CONCENTRATED PHOTOVOLTAICS - Arirohman, Ilham Dwi; Naimah, Khoirun; Syaukani, Muhammad; Sabar, Sabar (P3M Politeknik Negeri Indramayu, 2025)
Concentrated Photovoltaic (CPV) technology offers the potential to enhance solar energy conversion by utilizing light focusing technology to increase the solar irradiation flux received by photovoltaic cells. On the other hand, as the solar energy density increases on a PV cell, the surface temperature of the PV also rises, which results in decreased energy conversion efficiency and the possibility of thermal fatigue. Therefore, a reliable cooling system is required for CPV. This study aims to evaluate the performance of a two-phase flow heat sink with ethyl acetate (C4H8O2) as the working fluid, which has a low boiling point and high heat of vaporization, making it quite effective for heat transfer. The method used is numerical simulation using Computational Fluid Dynamics (CFD) software. The simulation results show that the heat sink heat transfer effectiveness is 86.03%, with a thermal resistance value of 0.0073 . The highest temperature on the solid part is 105 showing an increasing trend but not significantly, while the average fluid temperature tends to remain constant at 55 . This indicates that the evaporation process is able to maintain the heatsink temperature at stable level.